1988
DOI: 10.1017/s0031182000058376
|View full text |Cite
|
Sign up to set email alerts
|

Immunization of cattle using varying infective doses of Theileria parva lawrencei sporozoites derived from an African buffalo (Syncerus caffer) and treatment with buparvaquone

Abstract: A Theileria parva lawrencei isolate in the form of a sporozoite stabilate, derived by feeding clean Rhipicephalus appendiculatus nymphal ticks on an African buffalo (Syncerus caffer) captured in the Laikipia District, Kenya, was inoculated into groups of cattle at dilutions between 10(0) and 10(-3). Groups of 3 cattle infected with 1 ml inocula at 10(0), 10(-1) and 10(-2) dilutions were treated with 2.5 mg/kg body weight of buparvaquone on day 0 and similar groups were left untreated to act as controls. An add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Currently, there are different strategies for the prevention and treatment of bovine theileriosis, namely, (i) targeting the tick vector by acaricide treatment (3) or (ii) targeting the parasite itself by vaccination, chemotherapy, or a combination of the two (4,5). The most efficacious vaccine approach for East Coast fever was developed many years ago and includes infection of cattle with T. parva sporozoites and immediate treatment with a drug that impairs the establishment of infection, such as oxytetracycline (6) or, alternatively, buparvaquone (BPQ), which is currently the only effective compound for the treatment of bovine theileriosis (7)(8)(9). BPQ is a hydroxynaphtoquinone related to parvaquone (10,11).…”
mentioning
confidence: 99%
“…Currently, there are different strategies for the prevention and treatment of bovine theileriosis, namely, (i) targeting the tick vector by acaricide treatment (3) or (ii) targeting the parasite itself by vaccination, chemotherapy, or a combination of the two (4,5). The most efficacious vaccine approach for East Coast fever was developed many years ago and includes infection of cattle with T. parva sporozoites and immediate treatment with a drug that impairs the establishment of infection, such as oxytetracycline (6) or, alternatively, buparvaquone (BPQ), which is currently the only effective compound for the treatment of bovine theileriosis (7)(8)(9). BPQ is a hydroxynaphtoquinone related to parvaquone (10,11).…”
mentioning
confidence: 99%
“…It would appear from a comparative study that buparvaquone treatment could be safer than oxytetracycline in the control of more virulent theilerial stocks (Mutugi et al, 1988a). In this field study a single treatment with buparvaquone proved equally satisfactory as two treatments of Terramycin LA in controlling a virulent T. p. lawrencei stock (St 2306, Ngong 1).…”
Section: Discussionmentioning
confidence: 78%
“…In a study where cattle were immunised against a virulent T. p. lawrencei parasite, buparvaquone controlled higher doses of this parasite stock (Mutugi et al, 1988a) better than both short-and long-acting oxytetracycline formulations as shown in a comparative immunisation study (Mutugi, Young, Maritim, Ndungu, Stagg, Grootenhuis and Leitch, 1988b) where the same parasite stock was used.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such an approach has long been developed to vaccinate against theileriosis, with cattle being inoculated with live sporozoites and immediately treated with buparvaquone, the only drug currently available against Theileria parva and Theileria annulata, so far. 46,47 Another model could consist in applying suitable chemotherapeutics together with polypeptides acting as classical vaccines or immune-stimulators. Recombinant proteins produced in E. coli or via another suitable expression system may contain impurities and are very expensive, especially when produced in high purity at large scales.…”
Section: Toward a Strategy Against Neosporosismentioning
confidence: 99%